The Impact of Experiential Avoidance and Event Centrality in Trauma-Related Rumination and Posttraumatic Stress. Issue 6 (November 2018) - Bishop, Lia S.; Ameral, Victoria E.; Palm Reed, Kathleen M.
Cognitive control strategies like rumination often increase posttraumatic stress disorder (PTSD) symptoms. However, extant research has provided equivocal results when attempting to explain why this phenomenon occurs. The current study explored several mechanisms that may clarify such findings. For this study, 193 trauma-exposed community members completed measures of PTSD, rumination, experiential avoidance, and event centrality. Elevated reports of rumination were associated with greater PTSD symptomology, experiential avoidance, and event centrality. Results suggest that rumination indirectly influenced PTSD symptom severity through experiential avoidance. This pattern held true regardless of whether a trauma survivor viewed their reported trauma as central or peripheral to their personal identity. These data suggest that the link between ruminating about a traumatic experience and enhanced PTSD symptomology may be partially explained by increasingly restrictive cognitive patterns and enhanced avoidance of aversive internal stimuli. Furthermore, they provide preliminary evidence to suggest that rumination and experiential avoidance are strongly associated with one another (and subsequent PTSD symptomology) among trauma survivors, regardless of how central a traumatic event is to an individual's personal narrative. Such findings support clinical interventions like exposure, which progressively support new learning in response to feared or unwanted experiences in service of expanding an individual's cognitive and behavioral repertoires.